Vaccines against leishmaniasis: using controlled human infection models to accelerate development. (2nd November 2021) - Parkash, Vivak; Kaye, Paul M.; Layton, Alison M; Lacey, Charles J
ABSTRACT: Introduction: Leishmaniasis is a neglected tropical disease that is defined by the World Health Organization as vaccine preventable. Although several new candidate vaccines are in development, no vaccine has successfully reached the market for human use. Several species of Leishmania cause human disease and have co-evolved with their respective sand fly vectors. These unique relationships have implications for initiation of infection and vaccine development. An approach to vaccine development for many infectious diseases is the use of controlled human infection models (CHIMs). Areas covered: We describe the history and recent development of experimental and deliberate infection using Leishmania in humans and the rationale for developing a new sand fly-initiated CHIM to progress leishmaniasis vaccine development. Examples from other infectious diseases are discussed in the context of the development of a new leishmaniasis CHIM. We also reflect upon the manufacture of the challenge agent, practical considerations, safety, ethics, and regulatory issues. Expert opinion: A new cutaneous Leishmania CHIM is being developed to enable testing of vaccines in the development pipeline. Questions remain about the use of such CHIMs to determine effectiveness of vaccines against visceral leishmaniasis. However, such a CHIM will be invaluable in expediting time to market for vaccines.